The United States and Latin America the U.S. Foreign Policy and the Need for a New Direction - Torres Roldan, Alba Lorena; Maslowski, Nicolas, 1972-; Durrmeyer, Sébastien; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
No other region in the world has been more intervened by the United States than Latin America. An increasing interdependence between both in terms of trade, security and energy has grown along with a new reality. New political currents in Latin America have favored to recover the sovereignty and self-determination of their countries, while gaining independence from the United States preferences and mandates. The aim of this paper is to analyze the historical approach of the U.S. foreign policy to Latin America since 1945 as well as the implementation of them, with the purpose of evaluate the current scenario. A rhetoric vs reality approach is conducted showing the need for a more coherent U.S. foreign policy both in the economic and the security agenda.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses